Effects of footshock stress on social behavior and neuronal activation in the medial prefrontal cortex and amygdala of male and female mice - Mariia Dorofeikova; Chandrashekhar D. Borkar; Katherine Weissmuller; Lydia Smith-Osborne; Samhita Basavanhalli; Erin Bean; Avery Smith; Anh Duong; Alexis Resendez; Jonathan P. Fadok (PLoS ONE, 2023)
Social behavior is complex and fundamental, and its deficits are common pathological features for several psychiatric disorders including anxiety, depression, and posttraumatic stress disorder. Acute stress may have a negative impact on social behavior, and these effects can vary based on sex. The aim of this study was to explore the effect of acute footshock stress, using analogous parameters to those commonly used in fear conditioning assays, on the sociability of male and female C57BL/6J mice in a standard social approach test. Animals were divided into two main groups of footshock stress (22 male, 24 female) and context exposed control (23 male and 22 female). Each group had mice that were treated intraperitoneally with either the benzodiazepine—alprazolam (control: 10 male, 10 female; stress: 11 male, 11 female), or vehicle (control: 13 male, 12 female; stress: 11 male, 13 female). In all groups, neuronal activation during social approach was assessed using immunohistochemistry against the immediate early gene product cFos. Although footshock stress did not significantly alter sociability or latency to approach a social stimulus, it did increase defensive tail-rattling behavior specifically in males (p = 0.0022). This stress-induced increase in tail-rattling was alleviated by alprazolam (p = 0.03), yet alprazolam had no effect on female tail-rattling behavior in the stress group. Alprazolam lowered cFos expression in the medial prefrontal cortex (p = 0.001 infralimbic area, p = 0.02 prelimbic area), and social approach induced sex-dependent differences in cFos activation in the ventromedial intercalated cell clusters (p = 0.04). Social approach following stress-induced cFos expression was positively correlated with latency to approach and negatively correlated with sociability in the prelimbic area and multiple amygdala subregions (all p < 0.05). Collectively, our results suggest that acute footshock stress induces sex-dependent alterations in defensiveness and differential patterns of cFos activation during social approach.